Whiteness and Anti-Muslim Racism in Finland: The Racialisation of Finnish Muslim Converts - Hyökki, Linda (Context: Journal of Interdisciplinary Studies, 2022)
This article argues that the anti-Muslim experiences of Finnish converts should be analysed as racial, and that they have not emerged from a historical vacuum, but are rather embedded in a trajectory of racism in Finland. The article demonstrates this through the racialisation of the country’s national minorities, the Sámi and Roma peoples. Drawing on this, the article explains how the Finnish convert experience can be understood as a continuum of the racialisation of minorities in Finland, within the more extensive construction of Whiteness and normative Finnishness.